A CRITICAL STUDY TO CHECK THE AWARENESS OF RETAILERS OF SAUDI ARABIA AND OIL PRICE VOLATILITY IMPACT ON ECONOMIC GROWTH. - Robert J. Hanson (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Oil price fluidity is an ever-punctuated subject as oil transcends the import list of several countries and also is a major exporting item for relatively few countries. An apparent disequilibrium can be witnessed and thought of in this market with this mere statement. The present study intends to expound the awareness level of Saudi Retailers and identifying the association, if any, between oil fluctuations and economic growth. It is a comprehensive study carried out on a sample size of 100 respondents who are Saudi Retailers and were selected randomly to participate in this study. A well-developed questionnaire was contoured to collect data from the target group, and data was analyzed using SPSS Ver 19. The tools used in research include mean, percentage, standard deviation, one-sample t-test, and correlation. The key finding of the research postulates that there exists a positive correlation between the rise in oil prices and the fall of economic growth and vice versa.